ANALISIS STAKEHOLDERS DALAM PENGEMBANGAN DESTINASI WISATA PANTAI PASIR PUTIH WATES DI KABUPATEN REMBANG - Bagus Panuntun; Tri Yuniningsih; Mary Mangai (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2025)
Pasir Putih Wates Beach is one of the leading tourist destinations in Rembang Regency with strategic potential to support regional tourism development and improve local community welfare. However, its development has not yet been optimal due to problems related to stakeholder roles and inter-stakeholder synergy. This study aims to identify the stakeholders involved, analyze their respective roles, and examine the supporting and inhibiting factors influencing the development of Pasir Putih Wates Beach as a tourism destination. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, field observations, and documentation studies. The results indicate that 18 stakeholders are involved and can be classified into primary, key, and secondary stakeholders. Stakeholder roles are reflected in five main functions: policy creator, coordinator, facilitator, implementor, and accelerator. Overall, the roles of facilitators and accelerators have been relatively optimal, particularly those carried out by destination managers and the village government. However, the roles of policy creators, coordinators, and implementors have not been fully optimized due to limited budget allocation, the absence of destination revenue integration into local government revenue, limited formal authority of destination managers, minimal involvement of village-owned enterprises (BUMDes), and technical constraints related to accessibility and facilities. This study concludes that strengthening institutional governance, enhancing the integration of BUMDes roles, and establishing a cross-stakeholder collaboration forum are essential to support sustainable destination development.